The Influence of Workload and Job Satisfaction on Happiness at Work Among Employees of PT. Bakrie Pipe Industries - Puspita, Mugi; Purwadisastra, Dikdik; Japesa, Rian (Indonesian Scientific Publication, 2024)
This research aims to analyze the increase in workload and the influence of Workload and Job Satisfaction on Job Happiness in PT employees. Bakrie Pipe Industry. The method used is descriptive and verification with a quantitative approach. The research population was 248 employees of the Operations Division, and 104 respondents were selected using saturated sampling techniques. The research results show that Workload is in the very high category, Job Satisfaction is very low, and Job Happness is quite high. Based on the determination test, Workload influences Job Happiness by 2.2%, Job Satisfaction by 28.4%, and simultaneously Workload and Job Satisfaction influence Job Happiness by 32.6%. Partial hypothesis testing shows that Workload and Job Satisfaction have an influence on Job Happiness. Simultaneously, these two variables have also been proven to influence employee happiness at work.